Circadian regulation of epithelial functions in the intestine - Pácha, J; Sumová, A (Acta physiologica (Oxford, England), 2013)
Many physiological functions exhibit a diurnal rhythmicity that is influenced by biological clocks and feeding rhythms. In this review, we discuss the growing evidence showing the important role of circadian rhythms in regulating intestinal mucosa. First, we introduce the molecular timing system and the interrelationship between the master biological clock in the suprachiasmatic nuclei of the brain and the peripheral intestinal clock and provide evidence that the intestinal clock is entrained with the external environment. Second, we review the circadian rhythmicity of enterocyte proliferation and the largely unknown regulatory mechanisms behind these rhythms. Finally, we focus on the circadian clock control of food processing that functions by regulating the expression of digestive enzymes and intestinal nutrient and salt transporters. The concepts to be discussed highlight the ability of the intestinal epithelium to utilize self-sustained clock signals together with signals associated with changes in the cellular environment and to use endogenous temporal control of the gastrointestinal functions to meet varying physiological and pathophysiological demands. The fact that internal de-synchronizations within the body, such as those that occur in shift workers or with changes in food intake behaviour, are often associated with malfunctions of the gastrointestinal tract indicates that more information about the connections between the circadian clock and intestinal mucosa/transporting enterocytes could provide clues for future therapies.
Keywords: membránové transportní proteiny; signální transdukce; časové faktory; Cell Proliferation; Enteric Nervous System; Intestinal Absorption; střevní sliznice; lidé; gastrointestinální nemoci; Circadian Rhythm; intestinální absorpce; Signal Transduction; Humans; Cues; Enterocytes; Animals; Membrane Transport Proteins; proliferace buněk; přijímání potravy; Gastrointestinal Diseases; zvířata; cirkadiánní rytmus; Intestinal Mucosa; střevní nervový systém; Time Factors; nucleus suprachiasmaticus; enterocyty; podněty; trávení; Eating; Digestion; Suprachiasmatic Nucleus